Tanggung Jawab Negara Indonesia Terhadap Imigran Ilegal Kajian Hukum Keimigrasian - Unmehopa, Christiano K; Rehatta, Veriena Josepha Batseba; Leatemia, Wilshen (Faculty of Law, Universitas Pattimura, 2023)
Introduction: As a country with a strategic geographical position, Indonesia is often used as a stopover for immigrants.Purposes of the Research: The purpose of this paper is to study aims to find out and analyze the Immigration Law Regulating Illegal Immigrants and State Responsibilities to Illegal Immigrants Study of Immigration LawMethods of the Research: This type of research is normative juridical where the research is carried out by collecting primary, secondary and tertiary data obtained using library research. The data that has been collected is analyzed qualitatively, the description of which is arranged systematically based on legal disciplines to achieve clarity on the issues to be discussed.Results of the Research: The results of this study indicate that illegal/illegal immigrants in Indonesian immigration law have the same position as foreigners who enter and/or are in Indonesian territory. Illegal immigration itself is the movement of one person across the borders of a country where the movement has violated the immigration laws of the destination country. The responsibility of the State in handling illegal Immigrants is carried out by the Directorate of Immigration Investigation and Enforcement. For each province in Indonesia as an extension of the ministry of law and human rights there are regional offices of the Ministry of Law and Human Rights with an implementing unit in the field of immigration called the Immigration Division. Handling illegal immigrants, the sub-unit authorized to handle this is the Intelligence and Immigration Enforcement Division. The second is the Immigration Office where this agency is the first agency in handling illegal immigrants in the field. The third institution is the Immigration Detention Center as a place of quarantine or temporary detention of illegal immigrants